A quantitative trait locus, qSE3, promotes seed germination and seedling establishment under salinity stress in rice. (18th January 2019) - He, Yongqi; Yang, Bin; He, Ying; Zhan, Chengfang; Cheng, Yanhao; Zhang, Jiahui; Zhang, Hongsheng; Cheng, Jinping; Wang, Zhoufei
Summary: Seed germination is a complex trait determined by both quantitative trait loci (QTLs) and environmental factors and also their interactions. In this study, we mapped one major QTL qSE3 for seed germination and seedling establishment under salinity stress in rice. To understand the molecular basis of this QTL, we isolated qSE3 by map‐based cloning and found that it encodes a K + transporter gene, OsHAK21 . The expression of qSE3 was significantly upregulated by salinity stress in germinating seeds. Physiological analysis suggested that qSE3 significantly increased K + and Na + uptake in germinating seeds under salinity stress, resulting in increased abscisic acid (ABA) biosynthesis and activated ABA signaling responses. Furthermore, qSE3 significantly decreased the H2 O2 level in germinating seeds under salinity stress. All of these seed physiological changes modulated by qSE3 might contribute to seed germination and seedling establishment under salinity stress. Based on analysis of single‐nucleotide polymorphism data of rice accessions, we identified a HAP3 haplotype of qSE3 that was positively correlated with seed germination under salinity stress. This study provides important insights into the roles of qSE3 in seed germination and seedling establishment under salinity stress and facilitates the practical use of qSE3 in rice breeding. Significance Statement: One major QTL qSE3 for rice seed germination and seedling establishment under salinity stress was map‐based cloned, which promotes seed germination under salinity stress by enhancing K + and Na + uptake, increasing ABA biosynthesis and ABA signaling responses and reducing H2 O2 levels in germinating seeds. The application of qSE3 might be useful for improving salinity tolerance and breeding varieties suitable for direct seeding in rice.